Factors associated with posttraumatic stress and anxiety among the parents of babies admitted to neonatal care: a systematic review - Reem Malouf; Sian Harrison; Victoria Pilkington; Charles Opondo; Chris Gale; Alan Stein; Linda S. Franck; Fiona Alderdice (BMC, 2024)
Abstract Background Posttraumatic stress (PTS) and anxiety are common mental health problems among parents of babies admitted to a neonatal unit (NNU). This review aimed to identify sociodemographic, pregnancy and birth, and psychological factors associated with PTS and anxiety in this population. Method Studies published up to December 2022 were retrieved by searching Medline, Embase, PsychoINFO, Cumulative Index to Nursing and Allied Health electronic databases. The modified Newcastle-Ottawa Scale for cohort and cross-sectional studies was used to assess the methodological quality of included studies. This review was pre-registered in PROSPERO (CRD42021270526). Results Forty-nine studies involving 8,447 parents were included; 18 studies examined factors for PTS, 24 for anxiety and 7 for both. Only one study of anxiety factors was deemed to be of good quality. Studies generally included a small sample size and were methodologically heterogeneous. Pooling of data was not feasible. Previous history of mental health problems (four studies) and parental perception of more severe infant illness (five studies) were associated with increased risk of PTS, and had the strongest evidence. Shorter gestational age (≤ 33 weeks) was associated with an increased risk of anxiety (three studies) and very low birth weight (< 1000g) was associated with an increased risk of both PTS and anxiety (one study). Stress related to the NNU environment was associated with both PTS (one study) and anxiety (two studies), and limited data suggested that early engagement in infant's care (one study), efficient parent-staff communication (one study), adequate social support (two studies) and positive coping mechanisms (one study) may be protective factors for both PTS and anxiety. Perinatal anxiety, depression and PTS were all highly comorbid conditions (as with the general population) and the existence of one mental health condition was a risk factor for others. Conclusion Heterogeneity limits the interpretation of findings. Until clearer evidence is available on which parents are most at risk, good communication with parents and universal screening of PTS and anxiety for all parents whose babies are admitted to NNU is needed to identify those parents who may benefit most from mental health interventions.